The level of understanding on corruption among the civil servants at UiTM Puncak Alam / Alia Nadira Johan - Johan, Alia Nadira (2019)
Corruption is an issue that had existed since long time ago which normally involves the civil servants as they have power in any of the public section. As the other countries, Malaysia also has the specific law towards corruption crime and the convicted person will be punish with just and fair. Corruption is not a rare thing to be heard in a community eventhough it has been prohibited by legal law and Islam. Hence, to understand the understanding of individual on corruption, limited studies had been conducted. Therefore, this paper aims to study on the level of understanding on corruption among the civil servants in Uitm Puncak Alam. This study utilizes a quantitative research design by using the questionnaire that had been distributed towards the selected UiTM Puncak Alam staff. The findings of this study indicate that majority of the civil servants in UiTM Puncak Alam have a great level of understanding towards corruption. However, it is the best if the awareness towards corruption is spread widely towards all civilians.